From intermittent to continuous service: Costs, benefits, equity and sustainability of water system reforms in Hubli-Dharwad, India. (September 2018) - Burt, Zachary; Ercümen, Ayşe; Billava, Narayana; Ray, Isha
Highlights: Upgrading from intermittent to continuous water services affects net-benefits, sustainability and equity. In Hubli-Dharwad, India, household-level financial and time savings were neutral to positive in all wealth categories. System-level net present value (NPV) was negative when including the costs of supply augmentation. Equal cost recovery across all users resulted in a negative NPV for lower-wealth households. Capital or capacity constraints may force a trade-off between positive NPV and scale-up of continuous supply. Abstract: Urban service provision falls somewhere on the continuum of lower-cost, lower-quality, unreliable and intermittent to higher-cost, higher-quality, reliable and continuous. Piped water services in India are generally in the former category, but efforts are underway in some cities to shift to continuous supply. We use a matched-cohort research design to evaluate one such effort: an upgrade to continuous water service in a pilot zone of Hubli-Dharwad, India, while the rest of the city remained on intermittent services. We conducted a survey of ∼4000 households with four rounds of data collection over 15 months. We evaluated the household-level net benefits, the equity of their distribution, and the affordability of water access under continuous supply. We also evaluated the project at the system-level (household and utility), estimating the net present value of the upgrade and the feasibility of scale-up to the entire city. We found positive net benefits for households overall, but uneven distribution of these benefits across socio-economic strata. We also found that the costs of supply augmentation, a necessary step for scale-up, significantly reduced the project net present value. The potential for scale-up is thus unclear.